Supplemental Mental Health Treatment for Batterer Program Participants in Pittsburgh, Pennsylvania, 2004-2007 - Gondolf, Edward W. ([Verlag nicht ermittelbar], 2013)
The study was conducted to investigate the extent of mental health screening, referral compliance, and treatment effectiveness of men enrolled in batterer counseling programs. Specifically, the study looked at treatment compliance and effectiveness among men referred for mental health treatment in a program for men in Pittsburgh, Pennsylvania who were court ordered to receive batterer counseling, from 2004 to 2006. The final sample includes a total of 992 men, 478 men who were referred to treatment and 514 men who were not. The study included a service-delivery evaluation of the screening and referral and an outcome evaluation of the supplemental mental health counseling. The outcome evaluation was based on a quasi-experimental design comparing a subsample of men under a mandatory referral to those under a voluntary referral, and also men who actually obtained mental health treatment to those who were referred but untreated. Data were collected using questionnaires administered to both the men and their female partners over a 12 month period following intake into the counseling program, as well as clinical and arrest records to assess the extent to which the men complied with the referrals, their responses to the referral, and the outcomes from participation in the program, measured in terms of re-assault of their female partners.